Removing crosstalk effect for high efficient polymer light emitting diode display - Kacar, Rifat; Serin, Ramis Berkay; Ucar, Esin; Ulku, Alper (Pergamon-Elsevier Science Ltd, 2022)
For passive matrix organic light emitting diodes, crosstalk effect is serious problem. This problem adversely affects the image quality of display with driver circuit operation. In this study, 16x16 pixel monochrome green emissive passive matrix (PM) OLED Display Module was successfully fabricated which exhibits high efficiency, high luminance uniformity and MIL-STD-3009 night vision (NVIS) compatibility. Current efficiency, power efficiency and external quantum efficiency has been obtained as 22.79 cd/A, 10.23 lm/W and 4.61%, respectively. Additionally, crosstalk effect was removed by adjusting spin rate of the hole injection layer so that display image quality optimally has been achieved.
Keywords: Organic semiconductors; Optoelectronics devices; OLED display fabrication; Polymer light emitting diode; Crosstalk effect; Night vision compatibility; MIL-STD-3009